2020
DOI: 10.1051/0004-6361/201935814
|View full text |Cite
|
Sign up to set email alerts
|

A new equation of state applied to planetary impacts

Abstract: We present a new analytical equation of state (EOS), which correctly models high pressure theory and fits well to the experimental data of ɛ-Fe, SiO2, Mg2SiO4, and the Earth. The cold part of the EOS is modeled after the Varpoly EOS. The thermal part is based on a new formalism of the Gruneisen parameter, which improves behavior from earlier models and bridges the gap between elasticity and thermoelasticity. The EOS includes an expanded state model, which allows for the accurate modeling of material vapor curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…However, we believe that the effect is less significant than the effect of the type of EoS. Hard-sphere EoS Wissing and Hobbs (2020a).…”
Section: Modified M-aneos (Stewart Et Al 2020)mentioning
confidence: 85%
See 4 more Smart Citations
“…However, we believe that the effect is less significant than the effect of the type of EoS. Hard-sphere EoS Wissing and Hobbs (2020a).…”
Section: Modified M-aneos (Stewart Et Al 2020)mentioning
confidence: 85%
“…Karato (2014) and Hosono et al (2019) demonstrated the importance of unique thermodynamic properties of silicate melts in controlling the fate of a giant impact. However, there have been a few new papers on the issues of EoS in a giant impact (e.g., Stewart et al, 2020;Wissing & Hobbs, 2020b, 2020a) that presented somewhat different EoSs and pointed out a problem in Hosono et al (2019)'s treatment of EoS across the solid vapor transition.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations